The Role Of Akidah Akhlak Teachers In Shaping Student Discipline At MTs Al Manar - Zuhri, M. Syaifudin; Wajdi, Muh Barid Nizarudin; Soraiya, Soraiya; Putra, Miftakhul Ilmi Suwignya; Ummah, Vina Rohmatul (STAI Miftahul Ula Nganjuk, 2024)
The role of Akidah Akhlak teachers in shaping student discipline at MTs Al Manar Tanjungtani Prambon Nganjuk is the primary focus of this study. Employing a descriptive qualitative approach, the research explores the implementation of disciplinary practices, the strategies utilized by teachers to promote discipline, and the supporting factors that enhance the effectiveness of character education within the institution. Data were collected through direct observation, interviews with credible sources, and document analysis. The findings reveal that Akidah Akhlak teachers hold a strategic position in guiding students to become morally upright and responsible individuals. Various strategies are employed, including setting exemplary behavior, consistently mentoring and directing students, offering motivation and rewards for positive conduct, and applying wise corrective measures when necessary. The success of these efforts is strongly supported by a conducive school environment, the existence of clear institutional regulations, and the collaboration between the school and the surrounding community. The cultivation of discipline is not only intended to establish orderly behavior but also to reinforce the students' moral character, nurturing a generation with high integrity. Through well-planned strategies and a supportive educational atmosphere, Akidah Akhlak teachers at MTs Al Manar successfully integrate character education into daily school life, embedding discipline as a fundamental aspect of both school culture and student identity